Development of an oral recombinant chancroid vaccine delivered by attenuated Salmonella typhimurium SL3261 - Breau, Cathy (University of Ottawa (Canada), 2009)
Chancroid, a sexually transmitted genital ulcer disease caused by the Gram-negative bacterium Haemophilus ducreyi, facilitates the acquisition and transmission of H1V. An effective vaccine against chancroid has yet to be developed. We hypothesize that a Salmonella vector-based vaccine, expressing H. ducreyi antigens, could confer protective immunity in the rabbit model of H. ducreyi infection. The H. ducreyi outer membrane hemoglobin receptor HgbA has been shown to be a suitable vaccine candidate. HgbA was expressed from S. typhimurium SL3261 (pnirBhgbA) but not from the control strain, S. typhimurium SL3261 (pnirB). After a single dose or three doses, at two-week intervals of the vaccine, no antibody response to HgbA was detected in the rabbit model. The vaccine administered was immunogenic and survived in vivo passage. In this small animal trial, we were unable to induce protective immunity against chancroid. We conclude that the vaccine does not confer protective immunity against chancroid.
Keywords: Biology, Microbiology.; Health Sciences, Immunology.